Regional-specific activation of phagocytosis in the rat brain in the conditions of sepsis-associated encephalopathy - Shulyatnikova, T. V.; Shavrin, V. O.; Шулятнікова, Тетяна Володимирівна; Шаврін, Володимир Олександрович; Шулятникова, Т. В.; Шаврин, В. А. (Запорізький державний медичний університет, 2021)
In the condition of sepsis-associated encephalopathy (SAE), the brain neuroinflammatory response is considered as one of the most critical mechanisms of tissue damage and impaired cerebral homeostasis. The main cell population of the brain responsible for the immune surveillance is microglia, and its phagocytic activity is a fundamental function providing both homeostatic and damaging properties. The aim of this study was to determine the immunohistochemical and ultrastructural specificity of the phagocytosis activation in different rat brain regions in the conditions of experimental sepsis. Materials and methods. The study was conducted in Wistar rats: 5 sham-operated animals and 20 rats with cecum ligation and puncture (CLP). The immunohistochemical study of CD68 expression in the cortex, white matter, hippocampus, thalamus, caudate/putamen was carried out in the period of 20–48 h postoperatively. The cerebral cortex was examined using transmission electron microscopy. Results. Beginning from the 20th h after CLP, there was a significant dynamic increase in the values of the relative area of CD68 expression, the number of immunopositive cells, as well as the percentage of immunopositive cells with amoeboid morphology in all animals of the CLP group, with a predominance of the indicators in the lethal group of rats. The highest levels of phagocytic activity were noted in the white matter and caudate/putamen in both the survived and non-survived animals. ltrastructurally, the microgliocytes of the lethal group were characterized by signs of actively phagocytic cells and extensive glial-neuronal interaction; phagocytosing microglia in the survived animals showed an active involvement in the processes of necrotic debris elimination into the vasculature. Conclusions. In the conditions of SAE, there is the early and dynamic increase in phagocytosis activation with the predominant localization in the brain white matter and caudate/putamen, which could conceivably indicate a special role of these brain areas in the mechanisms of neuroinflammatory response in the conditions of systemic inflammation. In the brain of non-survived animals, the phagocytosis indices are higher than in the group of survivors, which most likely indicates a natural response of microglia to more pronounced destructive processes, but it does not preclude a concurrent neurotoxic activity of CD68-positive cells on the surrounding tissue elements.

В умовах сепсис-асоційованої енцефалопатії (САЕ) внутрішньомозкову нейрозапальну відповідь вважають одним із головних механізмів тканинного пошкодження та порушення мозкового гомеостазу. Основна клітинна популяція мозку, що відповідає за імунну відповідь, - мікроглія, а її фагоцитарна активність - основна функція, яка забезпечує її гомеостатичні та пошкоджувальні властивості. Мета роботи - визначити імуногістохімічні й ультраструктурні особливості активації фагоцитозу в різних відділах мозку щурів в умовах експериментального сепсису. Матеріали та методи. Дослідження виконали на щурах лінії Вістар: 5 хибнооперованих тварин і 20 щурів із перев’язкою та пункцією сліпої кишки (CLP). Здійснили імуногістохімічне дослідження експресії маркера CD68 у корі, білій речовині, гіпокампі, таламусі, хвостатому ядрі/путамені в термін 20-48 годин післяопераційного періоду. За допомогою трансмісійної електронної мікроскопії дослідили кору великих півкуль. Результати. У термін від 20 годин післяопераційного періоду спостерігали істотне динамічне підвищення значень відносної площі експресії CD68, кількості імунопозитивних клітин, а також відсотка імунопозитивних клітин з амебоїдною морфологією в усіх тварин CLP групи з переважанням показників у щурів летальної групи. Найвищі показники активності фагоцитозу визначили в білій речовині та хвостатому ядрі/путамені у групі й померлих тварин, і тих, які вижили. Ультраструктурно для мікрогліоцитів померлих тварин характерні ознаки клітин, що активно фагоцитують, і поширеної гліо-нейрональної взаємодії; у тварин, які вижили, фагоцитуюча мікроглія показала активну участь у процесах елімінації некротичного детриту в судинне русло. Висновки. В умовах САЕ в паренхімі мозку відбувається раннє та динамічне зростання фагоцитарної активності клітин із переважанням процесу в білій речовині та хвостатому ядрі/путамені. Теоретично це може вказувати на особливу роль цих ділянок мозку в механізмах нейрозапальної відповіді в умовах системного запалення. У мозку тварин, які померли, показники фагоцитозу мають вищі значення порівняно з тваринами, які вижили. Найімовірніше, це свідчить про закономірну реакцію мікроглії на вираженіші процеси деструкції, але не виключає одночасний нейротоксичний вплив CD68-позитивних клітин на навколишню нервову тканину.

В условиях сепсис-ассоциированной энцефалопатии (САЭ) внутримозговой нейровоспалительный ответ считают одним из главенствующих механизмов тканевого повреждения и нарушения мозгового гомеостаза. Основная клеточная популяция мозга, отвечающая за иммунный ответ, - микроглия, а ее фагоцитарная активность является основополагающей функцией, обеспечивающей ее и гомеостатические, и повреждающие свойства. Цель работы - определение иммуногистохимических и ультраструктурных особенностей активации фагоцитоза в разных областях головного мозга крыс в условиях экспериментального сепсиса. Материалы и методы. Исследование проведено на крысах линии Вистар: 5 ложнооперированных животных и 20 крыс с перевязкой и пункцией слепой кишки (CLP). Проведено иммуногистохимическое исследование экспрессии маркера CD68 в коре, белом веществе, гиппокампе, таламусе, хвостатом ядре/скорлупе в срок 20-48 ч послеоперационного периода. С помощью трансмиссионной электронной микроскопии исследована кора больших полушарий. Результаты. В срок после 20 часов послеоперационного периода отмечают существенное динамическое повышение значений относительной площади экспрессии CD68, количества иммунопозитивных клеток, а также процента иммунопозитивных клеток с амебоидной морфологией у всех животных CLP группы с преобладанием показателей у крыс летальной группы. Наиболее высокие показатели активности фагоцитоза отмечены в белом веществе и хвостатом ядре/скорлупе в группе и умерших, и выживших животных. Ультраструктурно для микроглиоцитов группы умерших животных характерны признаки активно фагоцитирующих клеток и распространенное глио-нейрональное взаимодействие; у выживших животных фагоцитирующая микроглия показала активное участие в процессах элиминации некротического детрита в сосудистое русло. Выводы. В условиях САЭ в мозге отмечено раннее и динамическое нарастание признаков активации фагоцитоза с преимущественной локализацией в белом веществе и хвостатом ядре/скорлупе. Предположительно, это может указывать на особую роль этих областей мозга в механизмах нейровоспалительного ответа в условиях системного воспаления. В мозге умерших животных показатели фагоцитоза имеют более высокие значения по сравнению с группой выживших. Скорее всего, это свидетельствует о закономерной реакции микроглии на более выраженные процессы деструкции, но не исключает одновременное нейротоксическое воздействие CD68-позитивных клеток на окружающую нервную ткань.
Регіональні особливості активації фагоцитозу в мозку щурів в умовах сепсис-асоційованої енцефалопатії
Региональные особенности активации фагоцитоза в мозге крыс в условиях сепсис-ассоциированной энцефалопатии
Keywords: sepsis-associated encephalopathy; phagocytosis; microglia; CD68; transmission microscopy election; сепсис-асоційована енцефалопатія; фагоцитоз; мікроглія; просвічуюча електронна мікроскопія; сепсис-ассоциированная энцефалопатия; микроглия; просвечивающая электронная микроскопия